Membrane fractionation of Cynara cardunculus swine blood hydrolysate: ingredients of high nutritional and nutraceutical value - Araújo-Rodrigues, Helena (2022)
This work proposes an innovative approach to valorise swine blood based on enzymatic hydrolysis and membrane fractionations. Hydrolysis with Cynara cardunculus enzymes, followed by microfiltration and double nanofiltration generated three high protein fractions, retentate of microfiltration (RMF; >0.5 µm) and retentate of nanofiltration (RNF; >3 kDa) with approximately 90% of protein on a dry basis and filtrate of nanofiltrate (FNF; <3 kDa) with 65%. FNF, rich in low molecular weight peptides, showed excellent antioxidants (ABTS and ORAC of 911.81 and 532.82 µmol TE g−1 DB, respectively) and antihypertensive (IC50 of 28.51 µg mL−1) potential. By peptidomics and in silico analysis, 43 unique sequences of interest were found, among which LVV-Hemorphin-7 was identified. This hemorphin was demonstrated as the main responsible for the observed bioactivity. Complementary results showed a prebiotic effect mainly for the growth of Bifidobacterium animalis Bo, as well as interesting free amino acids (mainly glutamic acid, leucine, alanine, phenylalanine and aspartic acid) and mineral (e.g., Ca, Mg, P, K and Na) profiles. No antibacterial effect was verified for the seven pathogenic bacteria tested. This study allowed obtaining new ingredient of high nutritional and nutraceutical value for human consumption, with a perspective of sustainability and industrial viability.